The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1537/ase.091007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for weapon-related traumas in medieval Japan: observations of the human crania from Seiyokan

Abstract: The Seiyokan site is located in Kamakura, Japan, and has yielded 91 human skeletons belonging to the 14-15th centuries AD. The purposes of this study are to examine the human crania from the archeological site at Seiyokan, to analyze the presence, distribution, and variability of their weaponrelated traumas, and finally to better understand violence in medieval Japan from osteological evidence. The results demonstrate that the traumas on the crania have morphological features consistent with human-induced cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Several preceding studies have shown that human skeletons from medieval Japan exhibited traumatic injuries related to violence, such as gashes, decapitations, blows, stabbing, and scratches (Suzuki et al, 1956;Morimoto, 1987;Morimoto and Hirata, 1992;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. The results of this study demonstrated the presence of weapon-related traumas on the cranium and limb bones.…”
Section: Weapon-related Traumassupporting
confidence: 57%
See 3 more Smart Citations
“…Several preceding studies have shown that human skeletons from medieval Japan exhibited traumatic injuries related to violence, such as gashes, decapitations, blows, stabbing, and scratches (Suzuki et al, 1956;Morimoto, 1987;Morimoto and Hirata, 1992;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. The results of this study demonstrated the presence of weapon-related traumas on the cranium and limb bones.…”
Section: Weapon-related Traumassupporting
confidence: 57%
“…Comparative samples for this study were cited from the literature on paleodemography (Nagaoka et al, 2006(Nagaoka et al, , 2012bNagaoka andHirata, 2007, 2008), dental caries (Sakura, 1964;Fujita, 1995;Ohshima, 1996;Todaka et al, 2003), enamel hypoplasia (Sawada, 2010), and violent behavior (Suzuki et al, 1956;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010Nagaoka, 2012) (Table 1). The chronological ages used in the comparative samples are the Jomon (14500-300 BC), Yayoi (300 BC-300 AD), medieval (1185-1573 AD), and Edo (1603-1687 AD) periods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medieval Kamakura and early-modern Kumejima peoples Intensive paleodemographic research has been performed and has revealed that the medieval Kamakura people were not long lived (Nagaoka et al, 2006;Nagaoka and Hirata, 2008). In addition, many weapon-related traumas were found among the skeletal remains from medieval Kamakura (Suzuki et al, 1956;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. However, there have been few studies on the life activity patterns of these people.…”
Section: People From Okhotsk Culturementioning
confidence: 99%